Pr??ticas de intelig??ncia coletiva no Portal de Peri??dicos da Capes - Silva, B??rbara Neves e (2017)
This study aims to evaluate the perception of information about the Capes Portal Periodicos (Scientific Digital Library), regarding the potential contribution of different practices and tools of Collective Intelligence (ICol) that can contribute to open science in Brazil. For the theoretical foundation of this aim, a literature review of the concepts of collective intelligence and open science was done, as well as the other ideas related to these topics (crowdsourcing and wisdom of the crowds). In this way, were identified ICol's main practices, routines, tools and collective intelligence processes to verify their potential impact to the collaboration of researchers from Brazil and that could be applied to open science and the main trends on the subject. Based on the information found in the literature, it was sought to understand how it is possible to increase collaboration among Brazilian researchers through Capes Digital Library, with the purpose of suggesting improvements within the scope of the Portal. For this purpose, a questionnaire was applied to students, professors, and collaborators of postgraduate courses from selected universities to measure their perception of ICol practices identified in the current literature. From the analysis of the results, it is recommended to insert the following methods in the Capes Digital Library: discussion forums, scientific blogs, wikis, and altmetrics. Finally, to validate the results obtained, interviews were conducted with specialists who have the strategic responsibility in the management of postgraduate programs and the dissemination of science. It was found that the respondents agreed with the suggested practices, although they had some caveats regarding their application. The suggestion is to connect these universes through the interoperability between search systems, in other words, inserting links from referral sites in wikis/ academic discussion forums as well as scientific blogs, in order to provide users with relevant information that can be of their interest. In the case of alternative metrics, the idea is to insert directly into the portal interface and provide researchers with information that can help them to share scientific results through the indicators produced in real time on the web.